OPPORTUNITIES OF HEDGING WITH FORWARD CONTRACT: EVIDENCES FROM CHITTAGONG STOCK EXCHANGE (CSE) - Chowdhury, Tasnim Uddin (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2022)
The stock market of Bangladesh is still in its development stage. No mechanism is there for the investors by which they can get protection against the variability of price that generates risk. A forward contract, an instrument of derivatives, gives the parties involved in the contract protection against such risk. This study investigates whether there is any opportunity of using forward contract or not for the investors trading at Chittagong Stock Exchange (CSE), one of the major stock exchanges of Bangladesh. To conduct the study, closing prices of 50 randomly selected companies operating under different sectors has been taken from the website of CSE for the period of September 2019. Then, the forward prices for December 2019 have been calculated by compounding the September prices at the rate of 91-day Treasury bill. Actual December 2019 prices are then compared to the calculated forward prices. The study finds significant difference between the actual price and calculated forward price for 94 percent of the sample companies. This implies that, the investors of CSE could better off by hedging their position through forward contract if such mechanism were there in practice.